Catalytic reduction and reductive functionalisation of carbon dioxide with waste silicon from solar panel as the reducing agent. (27th May 2022) - Pramudita, Ria Ayu; Nakao, Kaiki; Nakagawa, Chihiro; Wang, Ruopeng; Mochizuki, Toshimitsu; Takato, Hidetaka; Manaka, Yuichi; Motokura, Ken
Abstract : Waste silicon wafer recovered from the solar panel production process acted as a reducing agent for reduction and reductive functionalization of CO2 with fluoride catalyst. Abstract : CO2 was successfully reduced using powdered waste silicon wafer as a reducing agent and a catalytic amount of tetrabutylammonium fluoride. The waste silicon wafers could be recovered during the production of solar panels or at the end of the product's life cycle. The catalytic reduction reaction occurred under atmospheric pressure of CO2 at 95 °C to produce formic acid at 68% yield based on CO2 . The reaction mechanism was investigated based on isotopic experiments and X-ray photoelectron spectroscopy analysis of powdered silicon. This reaction system has potential applications in methanol synthesis and the reductive functionalisation of amine to formamide.